Inferring the selection on genes of yeasts, schistosomes and amniotes - Oh, T (2008)
Research presented in this thesis focuses on using evolutionary rates to detect the fingerprint of natural selection. I have undertaken four studies that consider different branches of the eukaryotic tree: 1. Predicting positive selection in genes from five species of Saccharomyces genes. 2. Studying the constraints on both synonymous and non-synonymous sites of Saccharomyces genes. 3. Using evolutionary rate studies to investigate how schistosomes have adapted to their environment. 4. Associating gene evolution with the non-linear increase between amniotes' brain and body sizes. In the first project, I investigated protein coding sequences to identify genes and their amino acids that have been subject to positive selection. I show that Saccharomyces genes exhibiting strong evidence for positive selection are enriched in defence and growth functional categories. In the second study, I find that a set of Saccharomyces genes are both constrained at the non-synonymous sites and synonymous site, presumably to ensure the correct folding of the protein, irrespective of their expression levels. I also find that the majority of yeast genes are not biased with respect to codon usage, and investigate constraints on substitution rates at synonymous sites. The third project examines the evolutionary rates of schistosome genes. I show that stage-specific genes are under weaker selective pressures than genes expressed in many life stages. I predict that the fastest evolving stage-specific genes enable the pathogen to better adapt to its ever-changing environment. In the final project of this thesis, I ask whether evolutionary rate variation for brain-expressed/specific genes correlates with brain size (allometric) change in amniotes. I find that lineages with relatively large brains have faster evolutionary rates. However, I find that there is no region of the brain in which faster evolving genes of relatively large-brained animals are preferentially expressed.